DESAIN GEDUNG KARYA PASTORAN ST. FRANSISKUS XAVERIUS, PAROKI TANJUNG PRIOK - Trisno, Rudy; Nathaniel Avelino; Steven Lim (Jurnal Serina Abdimas, 2025)
The main problem in constructing the Pastoral Works Building (GKP) of St Francis Xaverius Parish in Tanjung Priok is the limited land available, so the building design must be able to optimally accommodate the needs of partners. The solution to this challenge is realised through designing a new building by following six stages, namely: 1) Examining the use of symbols, icons, and indexes; 2) Examining pastoral buildings based on certain philosophies; 3) Making St Fransiskus Xaverius as the main identity of GKP; 4) Carrying out the design theme in the form of a sailing ship metaphor and batik icons from five ethnicities-Java, North Sumatra, North Sulawesi, East Nusa Tenggara, and Chinese; 5) Considering the bird's eye view from the highway towards the design location; 6) Compiling complete drawings in the form of plans, views, and pieces of the GKP. The conclusion of the design process was the integrated application of the six steps, which materialised in the complete architectural drawings. Details include: 1) Interpretation of symbols, icons, and indexes in the GKP building; 2) Philosophical analysis based on the thoughts of Kisho Kurokawa, Christian Norberg-Schulz, and Martin Heidegger; 3) Affirmation of the building's identity according to the patron saint, Fransiskus Xaverius; 4) Application of the theme of sailing ships and batik icons from five ethnicities on the building's facade; 5) Attention to the visualisation of the building from a bird's eye view; 6) Preparation of comprehensive building plans, views, and sections. Thus, the design of the Pastoral Works Building is expected to fulfil partners' needs and positively contribute to all related parties. ABSTRAK Permasalahan utama dalam pembangunan Gedung Karya Pastoral (GKP) Gereja St. Fransiskus Xaverius Paroki Tanjung Priok adalah keterbatasan lahan yang tersedia, sehingga perancangan gedung harus mampu mengakomodasi kebutuhan mitra secara optimal. Solusi atas tantangan ini diwujudkan melalui perancangan gedung baru dengan mengikuti enam tahapan, yaitu: 1) Mengkaji penggunaan simbol, ikon, dan indeks; 2) Menelaah bangunan pastoral berdasarkan filosofi tertentu; 3) Menjadikan Santo Fransiskus Xaverius sebagai identitas utama GKP; 4) Mengusung tema perancangan berupa metafora kapal layar dan ikon batik dari lima etnis-Jawa, Sumatera Utara, Sulawesi Utara, Nusa Tenggara Timur, dan Tionghoa; 5) Mempertimbangkan pandangan bird eye view dari jalan raya terhadap lokasi perancangan; serta 6) Menyusun gambar lengkap berupa denah, tampak, dan potongan GKP. Kesimpulan dari proses perancangan ini adalah penerapan enam langkah tersebut secara terpadu, yang terwujud dalam gambar arsitektural lengkap. Rinciannya meliputi: 1) Pemaknaan simbol, ikon, dan indeks pada bangunan GKP; 2) Analisis filosofis berdasarkan pemikiran Kisho Kurokawa, Christian Norberg-Schulz, dan Martin Heidegger; 3) Penegasan identitas gedung sesuai santo pelindung, Fransiskus Xaverius; 4) Pengaplikasian tema kapal layar dan ikon batik dari lima etnis pada fasad bangunan; 5) Perhatian terhadap visualisasi bangunan dari sudut pandang bird eye view; dan 6) Penyusunan gambar denah, tampak, serta potongan bangunan secara menyeluruh. Dengan demikian, perancangan Gedung Karya Pastoral ini diharapkan mampu memenuhi kebutuhan mitra dan memberikan kontribusi positif bagi seluruh pihak terkait.